2013
DOI: 10.5430/jnep.v4n1p229
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to work-related sharp injuries among nurses in Nigeria

Abstract: Workplace conditions increase risks to health care workers especially nurses who stay longest with the patient in the hospital. The purpose of this study was to determine the exposure to work-related sharp injuries among nurses and their frequency of contact with needles and other sharp devices at work in a selected Teaching hospital in Nigeria. Two hundred and seventy five (275) registered nurses participated in the study. Questionnaires served as the study tool and were administered following due ethical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
3
2
Order By: Relevance
“…This finding was align with many international studies [ 6 , 10 , 13 ]. On the other hand, the current study finding was higher than the finding of studies done in Malawi (30.3%), Nigeria (23.1%), and India (30.1%) [ 12 , 19 , 21 ] and lower than the studies done in Egypt (62.3%), Nigeria (68.3%), Sarajevo, Bosnia and Herzegovina (61.1%), and Saudi Arabia (50.9%), [ 4 , 5 , 7 , 11 ]. The prevalence of needle stick and sharp object injury reported from the studies conducted in Addis Ababa, Arba Minch, Bahir Dar, Awi were 66%, 42%, 33% and 18.7%, respectively [ 14 – 17 ].…”
Section: Main Textcontrasting
confidence: 78%
See 1 more Smart Citation
“…This finding was align with many international studies [ 6 , 10 , 13 ]. On the other hand, the current study finding was higher than the finding of studies done in Malawi (30.3%), Nigeria (23.1%), and India (30.1%) [ 12 , 19 , 21 ] and lower than the studies done in Egypt (62.3%), Nigeria (68.3%), Sarajevo, Bosnia and Herzegovina (61.1%), and Saudi Arabia (50.9%), [ 4 , 5 , 7 , 11 ]. The prevalence of needle stick and sharp object injury reported from the studies conducted in Addis Ababa, Arba Minch, Bahir Dar, Awi were 66%, 42%, 33% and 18.7%, respectively [ 14 – 17 ].…”
Section: Main Textcontrasting
confidence: 78%
“…In developing countries, where the prevalence of HIV infection is the highest in the world, the number of needle stick injuries is also the highest. Additionally, African health care workers suffer an average of two to four needle stick injuries per year and physicians are much less likely to report a needle stick injury than other healthcare professionals [ 11 ]. Study revealed that, transitional and developing countries where unnecessary injection is common, the average number of health care injection per person is averagely estimated to be 3.7/year.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study in occupational exposure and behavior of health care workers in Ethiopia shows needle recapping as a major cause of NSI [11]. Our study showed a higher prevalence of needle recapping after use (44.7% (126)), which was greater than the studies conducted in Nigeria (35.3%) [24] and Northern Ethiopia (34.7%) [25]. HCWs who practiced needle recapping were 2.45 times more likely to experience an injury than who did not recap needles after use (AOR = 2.45, 95% CI 1.49, 4.03).…”
Section: Discussioncontrasting
confidence: 54%
“…For instance, the prevalence of needle recapping after use in this study was 44%, and of these, nearly one-third (30.5%) was recapping using two hands. The practice of recapping is higher in the studies in Nigeria (35.3%) [ 72 ]. In this study, injection (37.7%) and blood withdrawal (24.5%) were the major clinical activities that lead to NSSI in this study.…”
Section: Discussionmentioning
confidence: 99%